2020
DOI: 10.1208/s12248-019-0406-y
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutical Understanding of Excipient Variability on Drug Apparent Solubility Based on Drug Physicochemical Properties. Case Study: Superdisintegrants

Abstract: The presence of different excipient types/brands in solid oral dosage forms may affect product performance and drug bioavailability. Understanding the biopharmaceutical implications of superdisintegrant variability (changes in material properties), variation (changes in excipient amount) and interchangeability (use of different excipient types with the same intended functionality) in oral drug performance would be beneficial for the development of robust final dosage forms. The current study investigated the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…The concentration of HPMC in this formulation (10%) was lower than the 'percolation threshold' reported in other studies [31,35] and may have contributed to the difference in swelling percentage observed in Figure 9B. Although HPMC concentrations as low as 10% (w/v) have been reported [18,[36][37][38], low levels of HPMC and high lactose content can be associated with sudden changes in matrix integrity and inconsistent results [38,39]. Substances with higher particle size require higher concentrations to percolate the tablet [39,40], so combining with a lower viscosity grade may improve tablet robustness.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The concentration of HPMC in this formulation (10%) was lower than the 'percolation threshold' reported in other studies [31,35] and may have contributed to the difference in swelling percentage observed in Figure 9B. Although HPMC concentrations as low as 10% (w/v) have been reported [18,[36][37][38], low levels of HPMC and high lactose content can be associated with sudden changes in matrix integrity and inconsistent results [38,39]. Substances with higher particle size require higher concentrations to percolate the tablet [39,40], so combining with a lower viscosity grade may improve tablet robustness.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition to having an unstable release, CR1 also had the weakest detachment force. CR6 and CR3 had higher HPMC concentrations (>24%) and the higher concentrations have also been found to increase mucoadhesive strength in previous studies [37,42]. Increasing the concentration of HPMC in tablet formulations increases the likelihood of chain entanglement between the hydroxyl groups and amide groups of the mucin layer [38].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The VIP is a weighted summary of the influence of each individual variable on the PLS model. The VIP is calculated as a weighted sum of the squares of the PLS loadings for each variable, which are representations of the variables impact and its correlations in the model, taking into account the amount of Y-variance explained ( 9 11 ) .…”
Section: Methodsmentioning
confidence: 99%
“…In the PLS-R analyses, the outliers were identified by comparison of the distance of each observation to the model in the Y-plane (DModY) with their calculated critical value (DCrit(Y)); an outlier is present if the standardized DCritY for an observation is greater than DCritY ( 9 11 ). Outliers were only exluded if (i) the PLS model improved significantly after exclusion and (ii) there was a clear scientific rational on why the data should be excluded ( i.e.…”
Section: Methodsmentioning
confidence: 99%